2016
DOI: 10.1016/j.yebeh.2016.02.041
|View full text |Cite
|
Sign up to set email alerts
|

A long-term noninterventional safety study of adjunctive lacosamide therapy in patients with epilepsy and uncontrolled partial-onset seizures

Abstract: This noninterventional, observational, postauthorization safety study (SP0942, NCT00771927) evaluated the incidence of predefined cardiovascular- (CV) and psychiatric-related treatment-emergent adverse events (TEAEs), in patients with epilepsy and uncontrolled partial-onset seizures, when initiating adjunctive therapy with lacosamide or another approved antiepileptic drug (AED) according to standard medical practice. Active recording of predefined TEAEs of interest took place at three-monthly recommended visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
3
15
0
2
Order By: Relevance
“…Following approval, there was an open-label, multicenter, non-interventional study conducted using a physician-driven decision to prescribe adjunctive treatment with lacosamide (n = 511) or another marketed AED therapy (n = 493) to patients with POS (23). The primary end point of the study was frequency of predefined cardiovascular TEAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Following approval, there was an open-label, multicenter, non-interventional study conducted using a physician-driven decision to prescribe adjunctive treatment with lacosamide (n = 511) or another marketed AED therapy (n = 493) to patients with POS (23). The primary end point of the study was frequency of predefined cardiovascular TEAEs.…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of clinical trials with a prospective or descriptive study design and a total number of more than 1500 enrolled patients showed a >50% reduction in seizure frequency in 23-48.2% of patients [Wehner et al 2009;Garcia-Morales et al 2011;Stephen et al 2011;Husain et al 2012;Miro et al 2013;Novy et al 2013;Verrotti et al 2013;Villanueva et al 2013;Legros et al 2014;Borzi et al 2016;Lang et al 2016]. Seizure freedom under adjunctive therapy with LCM of up to 33% and a reduction of seizure frequency >90% in approximately 26% has been shown [Harden et al 2012;Steinhoff et al 2016]. In addition, several retrospective, descriptive or comparative trials confirmed these results, reporting a reduction in seizure frequency of >50% in up to 69% and an overall seizure freedom of up to 33% under treatment with LCM [Flores et al 2012;Harden et al 2012;Kamel et al 2013;Villanueva et al 2013].…”
Section: Post-marketing Surveillancementioning
confidence: 99%
“…In summary, the most common reported adverse effects (AEs) in post-marketing studies were similar to those reported in the RCTs. These included sedation, somnolence, fatigue, dizziness, nausea, unsteadiness, ataxia, headache and double vision [Flores et al 2012;Husain et al 2012;Kamel et al 2013;Novy et al 2013;Verrotti et al 2013;Villanueva et al 2013;Steinhoff et al 2016]. For details on common AEs, please refer to Table 4.…”
Section: Post-marketing Surveillancementioning
confidence: 99%
“…11,12 Clinical efficacy was shown in five doubleblind randomized controlled trials, 8,[13][14][15][16] and further safety and tolerability data were generated in extension [17][18][19] and postmarketing studies. 20,21 Due to its intravenous formulation that is bioequivalent with oral preparations and overall good tolerability of LCM, [22][23][24] this anticonvulsant was used as a second-line or third-line therapy in SE. H€ ofler and Trinka described in detail the first evidence on the use of LCM in SE between 2009 and 2012.…”
mentioning
confidence: 99%